2018
DOI: 10.3892/etm.2018.6920
|View full text |Cite
|
Sign up to set email alerts
|

Elevated methylation of cyclin dependent kinase inhibitor 2B contributes to the risk of coronary heart disease in women

Abstract: Cyclin dependent kinase inhibitor 2B (CDKN2B) encodes a cyclin-dependent kinase inhibitor that may enhance the formation of atherosclerotic plaques. The aim of the present study was to investigate the contribution of CDKN2B promoter methylation on the risk of coronary heart disease (CHD). The present results indicated a significant association between increased CDKN2B methylation and the risk of CHD (adjusted P=0.043). A breakdown analysis according to sex demonstrated that CDKN2B methylation was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Specifically, an increasing interest in circulating epigenetic molecules is providing novel findings that may aid physicians in a more accurate risk stratification [ 99 ]. DNA methylation is a pivotal contributor to a balanced immune response toward the graft, due to regulation by both the innate and adaptive immune systems, with primarily T cells as the key players of alloreactivity and targets for immunosuppressive drugs [ 27 , 28 ]. Interestingly, FOXP3 gene expression was significantly higher in biopsy samples of rejectors collected before rejection in comparison with non-rejectors, and showed the tendency to predict rejection events [ 20 ].…”
Section: Epigenetics and Risk Stratification Of Cvds: Network Medicinmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, an increasing interest in circulating epigenetic molecules is providing novel findings that may aid physicians in a more accurate risk stratification [ 99 ]. DNA methylation is a pivotal contributor to a balanced immune response toward the graft, due to regulation by both the innate and adaptive immune systems, with primarily T cells as the key players of alloreactivity and targets for immunosuppressive drugs [ 27 , 28 ]. Interestingly, FOXP3 gene expression was significantly higher in biopsy samples of rejectors collected before rejection in comparison with non-rejectors, and showed the tendency to predict rejection events [ 20 ].…”
Section: Epigenetics and Risk Stratification Of Cvds: Network Medicinmentioning
confidence: 99%
“…At the molecular level, trimetazidine can switch the metabolic cellular state from beta-oxidation toward glucose oxidation by inhibiting synthesis or carnitine-facilitated transport of fatty acids so that cardiomyocytes can obtain more energy [ 131 ]. Recently, it has been reported that trimetazidine may exert its cardio-protective role in women by affecting the DNA methylation profile of the cyclin dependent kinase inhibitor 2b (CDKN2B) gene [ 27 , 28 ]. Trimetazidine is being studied in a randomized controlled trial (NCT03273387) which aims to determine if 3 months of treatment (35 mg twice a day) combined with standard therapy can alter right ventricle function in PAH patients.…”
Section: Repurposed Drugs and Epitherapy In Cvds: Network Medicine Camentioning
confidence: 99%
“…Eight articles [48][49][50][51][52][53][54][55] investigated the associations between DNAm and CHD and MI. All studies applied a candidate-gene approach and included a total of 2,353 participants 1,010 women and 1,343 men from China, Italy and the Netherlands.…”
Section: Coronary Heart Diseasementioning
confidence: 99%
“…Amongst more than a dozen trace elements essential to the human body, iron ranks first both in value and in quantity. Cells have established various sophisticated mechanisms to control their iron homeostasis strictly, including ferritin (Ft) [5], transferrin (TF) [6], and various iron-regulating proteins [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Given the influence of iron, it is particularly necessary to regulate iron metabolism and maintain iron homeostasis in the human body. Management of iron metabolism requires complex and fine coordination of various proteins, and the more important ones are Ft [5], TF [6], hepcidin [8], and various iron ion regulatory proteins [7].…”
Section: Introductionmentioning
confidence: 99%